Low back pain among nurses in orthopedic and intensive care unit at Universiti Kebangsaan Malaysia Medical Centre: the incidence, impacts and level of disability - Ibrahim, Amirah Fatin; Yassin, Aslina; Karim, Jalina (2010)
Low Back Pain (LBP) is a common problem affecting people at some point in their lives especially among nurses worldwide as well as Malaysia. When it happens, LBP can make many everyday activities difficult to do. A cross-sectional descriptive study was carried out to identify the incidence of low back pain among nurses, its impact and level of disability of nurses with LBP. Furthermore, this study intends to evaluate the relationship between age, years of working, BMI and low back pain. Using simple random selection, 105 nurses working in Orthopedic unit and ICU at Pusat Perubatan Universiti Kebangsaan Malaysia were chosen as respondent in this study. The incidence, impact and level of disability of LBP were evaluated with Nordic Low Back Questionnaire and Oswestry Low Back Pain and Disability Questionnaire. Student t test for independent samples was used in data analysis by using SPSS. The finding showed that the incidence of low back pain in life time among nurses was 65.7%. The impacts of LBP on work (44.1%), leisure activity (30.9%), and change of duties (2.9%) were small. Total length of time LBP had prevented from doing normal work were highest in 1 to 7 days (53.6%). More than half nurses showed significant impacts in pain intensity, lifting, sleeping and travelling. Most nurses (87%) were having the minimal disability of doing daily life. No significant mean difference in age and BMI in nurses who has low back pain and nurses with no low back pain. However, there is significant mean difference in years of working in nurses who has low back pain and nurses with no low back pain working in the respective units (p<0.05). The use of lifting devices should be emphasized as a preventive measure of LBP among nurses.